Composite reagents for water treatment based on natural alginates - Zyhmant, A.V.; Vu Xuan, Minh; Hrynshpan, D.D.; Savitskaya, T.A.; Tsygankova, N. G.; Tran, D. Lam; Pham, T. Lan (Vietnam Journal of Science and Technology, 2025)
Compositions of composite reagents for water treatment based on inorganic coagulants and sodium alginate used as a flocculant have been developed. The dissolution time of coagulants based on aluminum compounds was established to be equal 0.2 - 0.4 min, the dissolution time of sodium alginate milled and fractionated on 0.25 mm sieves was determined to be 2.0 min. By controlling the dispersion degree of the composite reagent components, a consecutive release of the coagulant and flocculant (sodium alginate) into the treated water has been achieved. The process of mixing the reagents was shown to not affect the dispersion degree of the components and didn’t prevent their consecutive release. An increase in the residual aluminum content was found when using Al2(SO4)3 in the presence of sodium alginate. The effect has been eliminated by additional introduction of CaCl2 into the composite reagent. The introduction of sodium alginate into composite reagents has been established to make it possible to increase the sedimentation rate of aggregates obtained by the hydrolysis of Al2(OH)5Cl from 3.9 × 10-3 m/s to 17 × 10-3 m/s compared with the use of coagulant alone.